Myocardial injury in systemic lupus erythematosus and lupus nephritis: A silent threat - Eleni Moysidou; Maria-Anna Bazmpani; Alexandros Kallifatidis; Dimitrios Kotzadamis; Efstathios Pagourelias; Theodoros Karamitsos; Maria Stangou; Eleni Frangou (Clinical Kidney Journal, 2026)
Abstract Systemic lupus erythematosus (SLE) is associated with significant cardiovascular morbidity, with myocardial involvement representing one of the most clinically significant yet underrecognized cardiac manifestations, largely due to its frequently subclinical presentation and diagnostic complexity. Lupus nephritis (LN), a common and clinically significant manifestation of SLE, is further associated with increased cardiovascular risk, reflecting a dynamic cardiorenal interaction driven by persistent immune activation. Recent advances in cardiovascular imaging techniques have facilitated the early detection of myocardial injury in SLE, improving diagnostic accuracy and enabling timely intervention, but have also uncovered the increased possibility of subclinical, underdiagnosed cases. Herein, this review focuses on myocardial disease in SLE, outlining the diagnostic tools available for early detection of myocardial complications.